Community Drug Distributor Knowledge, Attitudes, and Motivation Surrounding Mass Drug Administration for Soil-Transmitted Helminths in India - Aruldas, Kumudha; Kaliappan, Saravanakumar Puthupalayam; Israel, Gideon John; Palanisamy, Gokila; Johnson, Jabaselvi; Titus, Angelin; Walson, Judd L.; Means, Arianna Rubin; Ajjampur, Sitara Swarna Rao (Frontiers in Public Health, 2021)
Background: DeWorm3 is an ongoing multi-country community-based cluster-randomized trial assessing the feasibility of interrupting transmission of soil-transmitted helminths (STH) with community-wide mass drug administration (cMDA). In Tamil Nadu, India, community drug distributors (CDDs) worked with DeWorm3 field staff to counsel community members and deliver door-to-door deworming treatment. As CDDs were likely to influence the successful delivery of cMDA, we describe drivers of CDDs’ knowledge, attitudes, and motivation towards the delivery of cMDA. Methods: In this convergent mixed-methods study, a questionnaire on STH and cMDA was administered to 104 CDDs and 17 focus group discussions (FGDs) were conducted. Key outcomes in the quantitative and qualitative analyses included CDDs’ knowledge about STH and cMDA and attitudes towards cMDA for STH. Univariate and multivariable logistic regression analyses were performed to determine the strength of associations between independent and outcome variables. The FGDs were analyzed using a priori thematic coding. Results: CDDs who completed at least secondary school education (adjusted odds ratio (aOR): 2.71, 95% CI: 1.16 – 6.33) and had prior experience in health programs (aOR: 2.72, 95% CI: 1.15 – 6.44) were more knowledgeable about STH and cMDA. CDDs belonging to the scheduled castes and scheduled tribes (aOR: 2.37, 95% CI: 1.04 – 5.39), and to households engaged in a skilled occupation (aOR: 2.77, 95% CI: 1.21 – 6.34) had a more positive attitude towards cMDA for STH. The FGDs showed that while there were myths and misconceptions about STH, many CDDs believed that the adult population in their communities were infected with STH, and that a door-to-door drug delivery strategy would be optimal to reach adults. Conclusions: Educational and socioeconomic backgrounds and experience in health programs should be considered while designing CDD trainings. Along with cMDA delivery for STH, CDD trainings should focus on addressing myths and misconceptions around STH to strengthen competency in counseling.